Genotypic and phenotypic variability of 22q11.2 microduplications: An institutional experience. Issue 11 (3rd September 2019) - Yu, Alexander; Turbiville, Donald; Xu, Fangling; Ray, Joseph W.; Britt, Allison D.; Lupo, Pamela J.; Jain, Sunil K.; Shattuck, Karen E.; Robinson, Sally S.; Dong, Jianli
Abstract: Duplications in the 22q11.2 region can cause 22q11.2 duplication syndrome and encompass a variety of phenotypes including developmental delays, facial abnormalities, cardiovascular defects, central nervous system delays, and other congenital abnormalities. However, the contribution of these contiguous duplicated regions to the clinical phenotypes has not been fully elucidated. In this study, we identified nine patients carrying different 22q11.2 microduplications detected by chromosomal microarray. Of these patients, seven pediatric patients presented with various clinical features including two neonate cases died shortly after birth, and two healthy adults. We examined region specific genotype–phenotype associations and found unpredictability associated with 22q11.2 duplications in these nine patients.